Integrating network pharmacology and in vitro model to investigate hippocampal neurotoxicity induced by atrazine. (4th May 2022) - Li, Jianan; Bi, Haoran
Abstract: Atrazine (ATR), a commonly applied herbicide in agriculture, has been found to cause hippocampal injury in rodents. However, the underlying toxicological targets and mechanisms are unclear. In this study, network pharmacology analysis and in vitro model were integrated to investigate the effect and mechanism of ATR-induced hippocampal neurotoxicity. In total, 71 targets of hippocampal neurotoxicity induced by ATR were predicted. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment (KEGG) enrichment analysis suggested that these targets were related to multiple GO terms and signaling pathways. To further investigate the underlying mechanisms, the top 10 hub targets were screened and included tumor protein p53 (Tp53), caspase 3 (Casp3), prostaglandin-endoperoxide synthase 2 (Ptgs2), cAMP-responsive element-binding protein 1 (Creb1), estrogen receptor 1 (Esr1), Jun proto-oncogene (Jun), brain-derived neurotrophic factor (Bdnf), catalase (Cat), sirtuin 1 (Sirt1) and Fos proto-oncogene (Fos). Moreover, the cell counting kit-8 (CCK8) and lactate dehydrogenase (LDH) assay showed that ATR had time and dose-dependent cytotoxicity on H19-7 cells. TUNEL staining revealed that ATR increased the apoptotic ratio. In addition, Real-time quantitative polymerase chain reaction (RT-qPCR) results indicated that the mRNA expression levels of all hub targets showed significant changes, except Esr1 and Jun. Our study demonstrated that ATR mainly acted on multiple targets and signaling pathways to exert its hippocampal neurotoxicity. These results provided initial evidence for the further exploration of the toxicological mechanism of ATR.